The influence of the Olympic Games on Beijing consumers' perceptions of their city tourism development - Kapareliotis, Ilias; Panopoulos, Anastasios; Panigyrakis, George G. (My University, 2010)
Purpose – The purpose of this paper is to explore the perceptions of the residents of Beijing for the improvement of the tourist infrastructure after the Olympic Games. The study identifies factors affecting the inhabitants' perceptions about the tourist impact of the Olympic Games, and the development of special tourist types. Design/methodology/approach – A group of 1,000 urban Beijing residents from different districts are personally interviewed on their perceptions about Beijing as a tourist destination. Their perceptions are measured on the basis of infrastructure improvements made for the Olympic Games, and the impact these improvements will have in Beijing as a post Olympic city. Findings – The Olympic Games improve tourist infrastructure according to Beijing residents. Infrastructure for the Olympic Games affects the economic development of the Olympic city, as well as the touristic development of the city. The above mentioned factors lead to three clusters of residents, namely the eco tourism supporters, the linked tourism supporters, and the mainstream tourism supporters. These three groups with different characteristics are responsible for tourist improvement, additionally to the development of new tourist models mostly related to the Olympic Games infrastructure. Practical implications – The improvement of tourist infrastructure in an Olympic City will attract different types of tourists who are not attached only to sports. Tourists interested in culture, in ecotourism, in linked tourism, and in mainstream tourism will also be attracted by an Olympic City. The outcomes of the study can be used by future Olympic cities in order to improve their image as a tourist destination. Originality value – There is limited research related to the impacts of the Olympic Games into the tourist industry. The present study identifies the impact of the Olympic infrastructure to different types of tourism. Different clusters of residents will provide valuable insights related to tourism stemming from the Olympic infrastructure. © 2010, Emerald Group Publishing Limited
Keywords: China; Cities; Olympic Games; Tourism